The Development of Temporal Concepts: Linguistic Factors and Cognitive Processes - Zhang, Meng; Hudson, Judith A. (Frontiers in Psychology, 2018)
Temporal concepts are fundamental constructs of human cognition, but the trajectory of how these concepts emerge and develop is not clear. Evidence of children’s temporal concept development comes from cognitive developmental and psycholinguistic studies. This paper reviews the linguistic factors (i.e., temporal language production and comprehension) and cognitive processes (i.e., temporal judgment and temporal reasoning) involved in children’s temporal conceptualization. The relationship between children’s ability to express time in language and the ability to reason about time, and the challenges and difficulties raised by the interaction between cognitive and linguistic components are discussed. Finally, we propose ways to reconcile controversies from different research perspectives and present several avenues for future research to better understand the development of temporal concepts.